1997
DOI: 10.1094/pdis.1997.81.5.481
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Geographic Distribution of Serotypes of Potato Virus Y

Abstract: From a panel of 10 monoclonal antibodies (MAbs) prepared against specific isolates representing the three recognized strain groups of potato virus Y (PVY), i.e., common (PVYO), tobacco veinal necrosis (PVYN), and stipple streak (PVYC), seven were selected for serotype analysis. These MAbs were tested for reactivity with 52 PVY strains representing all three strain groups from an international collection. Within the PVYN strain group, five serotypes were identified and designated N1 to N5. The PVYO strain group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 14 publications
3
20
0
2
Order By: Relevance
“…N found, giving additional evidence that PVY N strains are a recent introduction into the seed potato system in North America (24 (50,59,60,84) showed that some strains were molecular recombinants, while others were not.…”
Section: Pvymentioning
confidence: 92%
“…N found, giving additional evidence that PVY N strains are a recent introduction into the seed potato system in North America (24 (50,59,60,84) showed that some strains were molecular recombinants, while others were not.…”
Section: Pvymentioning
confidence: 92%
“…Reports of the PVY N strain have been recorded in South America, Europe, Africa, Asia (Weidemann, 1988b) and New Zealand (Fletcher, 1989). It is a quarantine pathogen in Canada and the United States (Ellis et al, 1997). The PVY N strain can cause severe veinal necrosis reaction in tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…It was responsible for severe potato crop damage in the 1950s and 1970s across many countries in Europe and resulted in yield reductions between 29% and 59% depending on the cultivar (Kurppa and Rajala, 1986). The PVY C strain has been identified in Europe, North America, India, South Africa, Australia, New Zealand and Ecuador (Ellis et al, 1997;Jeffries, 1998). Some PVY C isolates cannot be transmitted by aphids (Watson and Wilson, 1956;De Bokx et al, 1978;Blanco-Urgoiti et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…As estirpes de PVY C tem a sua distribuição mais reduzida do que os dois grupos citados e a sua caracterização é ambígua. Alguns isolados de PVY C causam reações de hipersensibilidade em cultivares de batata e outros não são transmissíveis por afídeos, fatores que limitam sua disseminação, influenciando a epidemiologia desta virose (Ellis et al, 1997). Embora alguns autores tenham observado variabilidade serológica entre estes grupos, não encontraram diferenças consistentes nos testes serológicos quando utilizaram anti-soros policlonais.…”
unclassified
“…Embora alguns autores tenham observado variabilidade serológica entre estes grupos, não encontraram diferenças consistentes nos testes serológicos quando utilizaram anti-soros policlonais. Porém, com a disponibilidade de anticorpos monoclonais, foi possível caracterizar serologicamente a maioria dos isolados (Rose et al, 1987;McDonald & Kristjansson, 1993;Ellis et al, 1997).…”
unclassified